Aspects of Crypto Currency’s Legislative Regulation. / Aspectos de la regulación legislativa de la moneda criptográfica - Prasolov, Valeriy I.; Kolesnikova, Anastasia S. (Utopía y Praxis Latinoamericana)
ABSTRACT The issues of legal and regulatory governance of a new type of electronic money crypto currency are considered in the article. It has been proved that there is no uniform understanding of the forms and methods of the crypto currency regulation in the world. The existing formulations of the concept of "crypto-currency" are analyzed in the article, on which bases the necessity of crypto currency’s adequate scientific understanding is identified and justified. As a result, of the study the main prerequisites for the legal regulation of the appearance and use of crypto-currency in payment systems are formulated by the authors. RESUMEN Las cuestiones de la gobernanza legal y regulatoria de un nuevo tipo de moneda criptográfica de dinero electrónico se consideran en el artículo. Se ha demostrado que no hay una comprensión uniforme de las formas y métodos de la regulación de la moneda criptográfica en el mundo. Las formulaciones existentes del concepto de "criptomoneda" son analizadas en el artículo, en el cual se basa la necesidad de la comprensión científica adecuada de la criptomoneda. Como resultado del estudio, los autores formulan los principales requisitos previos para la regulación legal de la aparición y el uso de la criptomoneda en los sistemas de pago.